Housing market in the Republic of Kazakhstan: current state and development prospects - Mambetova, S.Sh.; Shokhan, R.; Onayeva, B.T.; Abaidilda А.Е. (BUKETOV BUSINESS REVIEW, 2017)
There is a tendency of transition to socially oriented market economy at the present stage of development of the Kazakhstan society. At the same time, an important value is occupied by the problems of development of socially oriented industries. In the long term, housing market, as it promotes the solution of many social and economic tasks, can become one of socially -oriented branches in the Republic of Kazakhstan. The article deals with the problem of the housing market in the Republic of Kazakhstan. The main issues that emerged in the housing market, which are considered as an integral part of the real economy, were studied. In the course of the study, the main indicators of the industry such as finance, housing affordability ratio, housing price per square meter were analyzed. The main factors affecting housing prices were analyzed. At the same time, attention is paid to the policy of state regulation of the housing sector. The role and place of the housing market in the modern economy of the Republic of Kazakhstan is shown, as well as the steps the steps undertaking by the government to solve those problems, law acts and those fulfillment is being under consideration. Within the State Program of Regional Development till 2020, the prospects for further development of the housing market are shown. All the possible ways for solving housing problems in Kazakhstan are discussed in this article. All the possible ways for solving housing problems in Kazakhstan are discussed in this article.